Effect of Organic Nutrients on the Yield and Quality of Banana cv. Nendran (Musa spp., AAB) - Manju, P. R.; Pushpalatha, P. B. (International Journal of Bio-resource and Stress Management, 2022)
A study was undertaken at Banana Research Station, Kannara, Kerala Agricultural University, Thrissur, India during 2011−12 to 2017−18 in five seasons to standardize an organic nutrient schedule for Nendran banana. Eleven treatments involving various sources of organic nutrients (T1 to T10) were tried against inorganic source of nutrients as control (T11). T1 to T4 involved organic manures viz., FYM, neem cake, vermicompost and wood ash in different proportions. While T5 was absolute control, T6 and T7 included triple green manuring and biofertilizers alone respectively. T8 to T10 had organic manures along with triple green manuring or biofertilizers or both. The results showed that a combination of FYM (10 kg), neem cake (1.25 kg), vermicompost (5 kg), wood ash (1.75 kg), triple green manuring with cowpea and biofertilizers (AMF @ 25 g±Trichoderma harzianum @ 50 g±PSB @ 50 g±Azospirillum @ 50 g plant-1) recorded the highest bunch weight (9.60 kg) and yield (23.99 t/ha). The treatment was on par with inorganic fertilizer treatment and had a B:C ratio of 1.78. Better quality attributes in terms of extended shelf life and TSS was another notable advantage of the treatment. Soil health was also significantly improved in treatments involving organic nutrient sources as evident from the soil microbial population and enzymatic activity, when compared to inorganic control.